GAS HYDRATES EXTRACTION - Abdullah, N.; Pedchenko, M.; Pedchenko, N. (Збірник наукових праць Галузеве машинобудування будівництво, 2017)
The work is dedicated to alternative energy sources, namely extraction of methane gasfrom gas hydrate fields. In Ukraine they are represented by gas hydrate fields of the BlackSea. The technology of methane extraction from the sea gas hydrates is suggested. Threebasic methods of gas extraction from the gas hydrate-bearing reservoirs are known, namely:pressure reduction lower than the pressure equilibrium of hydrates formation at the designedtemperature; heating gas hydrate-containing rock to the temperature exceeding thetemperature balance; gas hydrate bearing formations disintegration. All the above methodsrequire high energy consumption. It is suggested to enrich sea gas hydrate-bearingformations directly in the field they underlay in. The purpose of the present study isdeveloping and analyzing the gas hydrates extraction method, which is characterized by theabsence of the phase transitions at gas hydrates extraction from the productive stratum and,consequently, by the increased versatility and the economical efficiency of the process.Separate steps of the enrichment process are set for this purpose. The suggested technologyrequires extracting the main bulk of gas hydrates without energy consumption for the phasetransition. Meanwhile, it is suggested to dissociate part of gas hydrate in the rock on accountof the sea water’s low potential energy.Keywords: gas hydrates, gas hydrates reservoir, dissociation, enrichment.Абдуллах